An Analysis Of Management As A Dynamic Function And Its Evolution And Adaptation To Changes In Economic, Socio-Political, Or Technological Environments - Susu, Wu; Bhaumik, Amiya (Journal of Neonatal Surgery, 2025)
An alternative approach to dynamic workplace management that promotes knowledge exchange is offered. Taking a proactive stance as a manager means shaping the workplace in real time. Workers move about the office in self-contained clusters, each with its own timetable for getting things done. Coordination of timing and organization of activities, as well as grouping tasks such that group members are physically close to one another and have access to relevant data for the intra-group task at hand, are two ways to guarantee that information is easily shared. Task sets and groups, their composition and structure, the order in which they occur, the temporal characteristics of tasks, and the naming conventions for data relevant to these tasks are all affected by the environment's dynamic nature. This is then achieved by applying a mathematical formulation to the issue. A clustering approach was developed by researchers to address issues. There are a lot of examples given so that students can understand the procedure completely. As a bonus, the proposed approach may be useful in the ever-changing administration of different types of resources required to complete the tasks